A gender perspective on self-employment entry and performance as self-employed - Pernilla Andersson Joona; Eskil Wadensjö (Institute for the Study of Labor (IZA), 2008)
Research on self-employment has increased during recent years and particular attention has been paid to self-employment dynamics and the factors influencing entry and exit rates from self-employment. Using a large panel data set for Sweden, this paper investigates variations in recruitment to self-employment and in self-employment performance by gender and by employment status prior to entering self-employment. As performance measures we use income from self-employment, number of employees, exit rates and destination after self-employment. We find that the probability of becoming self-employed is highest among men who are economically inactive and lowest among women who are wage-earners. Analysing self-employment performance, we find that men have higher incomes than women. Self-employed women more often than self-employed men have employees. For both men and women those who enter from unemployment or inactivity are less successful in terms of income and the probability of having employees than those who enter from paid employment. When exits are divided into paid employment and other employment status, we find that those who entered from unemployment or inactivity face a higher risk of returning to one of these states.
urn:nbn:de:101:1-2008071164
Keywords: J23; 330; Self-employment; unemployment; income; occupational mobility; gender differences; Selbstständige; Erwerbsverlauf; Geschlecht; Arbeitslosigkeit; Einkommen; Frauenerwerbstätigkeit; Schweden